Information and Communication Technologies in Education (Journal of Pedagogical Inventions and Practices, 2022)
This work is a description of information and communication technologies (ICT) used in education. The tasks solved through the introduction of ICT in the educational process are outlined. Based on the popularization of this type of technology in education, the advantages and disadvantages in obtaining the necessary knowledge are given.